The collector [compact disc, unabridged] - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2023)
Legendary art restorer and spy Gabriel Allon joins forces with a brilliant and beautiful master thief to track down the world's most valuable missing painting but soon finds himself in a desperate race to prevent an unthinkable conflict between Russia and the West.